GIS-BASED IDENTIFICATION AND ANALYSIS OF TRAFFIC ACCIDENT-PRONE ROAD SEGMENTS IN PALU CITY, INDONESIA - Sutrisno, Bambang (Jurnal Sains dan Teknologi Tadulako, 2026)
The purpose of this study is to identify road areas that are vulnerable to accidents in Kota Palu, to analyze road streets that are susceptible to crashes in kota Palu and to deal with road areas where accidents occur. The method used in the analysis of accident data from 2018 to 2021 for arterial roads and collectors in KotaPalu is the UCL (Upper Control Limit) method in ArcGIS 10.8 From the results of the analysis, then the road areas in Sulawesi with the function of Primary Artery Road, National Road Status, APW value (Accident Point Weightage) = 167 and UCL value ( Upper Control Limite) = 30.689, JL. RE Martadinata with function of primary artery road, National Street Status, the value of APW (accident point Weighage) = 60 and the value UCL(Upper control limit) = 24.675 and YL. The recommended mitigation of traffic accidents is by improving the awareness of road users in crossing with the introduction of driving safety and the installation of road facilities such as installation of traffic lights, installing traffic lamps, and paving roads carried out as soon as possible to minimize the occurrence of road accidents.